Crystals and crystalloids in cytopathology: Incidence and importance. Issue 10 (6th June 2022) - Torous, Vanda F.; Dodd, Leslie G.; McIntire, Patrick J.; Jiang, Xiaoyin Sara
Abstract : Many crystals and crystal‐like structures may be encountered in cytopathology practice and can represent both beautiful novelties and diagnostic aids. The authors present an organ‐specific review of the published literature on crystals combined with personal experiences. The purpose is not only to serve as a reference guide by highlighting the clinical and morphologic features of crystals, crystalloids, and crystal‐like structures but also to review their significance and to offer reporting strategies in cases that bear management implications. Abstract : Presented is an organ specific review of crystals, crystalloids, and crystal‐like structures. This review not only highlights their clinical and morphologic features but also their significance, particularly as potential diagnostic aids.